Successful Treatment of Hard Corns in Two Patients Using Microwave Energy - Ivan R. Bristow; Christopher J. Webb (Karger Publishers, 2020)
Corns are a common foot problem accounting for nearly half of all problems seen within podiatry and chiropody clinics. Hard corns are concentrated areas of hyperkeratosis within the stratum corneum, typically found on the weight-bearing (plantar) surfaces of the feet. For many patients, they are a source of pain and have been shown to negatively affect a patient's activity and quality of life. Most of the currently available treatments are short-lived in their effectiveness, with corns frequently being recurrent, requiring repeated visits to remove the painful lesions. The use of handheld microwave devices indicated for surface applications has demonstrated effectiveness in clearing recalcitrant plantar warts and significantly reducing the pain associated with them. The authors report 2 cases of patients with persistent and painful plantar corns who underwent microwave treatment of their plantar corns with a successful, lasting reduction in pain levels after the intervention. Further work is required to fully assess the potential of this treatment modality in the management of painful plantar corns.